Comparative Analysis of Type 1 and Type 2 Diabetes Mellitus: Assessing Demographics, Clinical Attributes and Risk Factors among Iraqi Patients (Bangladesh Journal of Infectious Diseases, 2026)
Background: Among the various forms of diabetes, Type 1 diabetes mellitus (T1DM) and Type 2 diabetes mellitus (T2DM) represent the most common and clinically significant categories.Objective: The objective of this retrospective comparison study was to find out the different between Type 1 Diabetes Mellitus and Type 2 Diabetes Mellitus in term of demographic information, clinical features, risk factors and consequences.Methodology: This retrospective comparison study was performed on 300 confirmed diabetes patients (T1DM and T2DM) extracted from medical records at a specialized diabetic clinic, Iraqi patients. Demographic data, clinical characteristics, risk factors and complications data was collected from May 2025 to May 2025.Results: A lot more people had type 2 diabetes (70.0%) of all cases than type 1 diabetesType 1 diabetes mostly affected younger people (mean age ± SD: 18.4 ± 6.2 years), while Type 2 diabetes mostly affected adults in their 40s and 50s (n = 48, 53.3%). A strong association was observed between overweight status and the development of Type 2 diabetes. People with Type 2 diabetes were more likely to have long-term problems.Conclusion: Type 1 diabetes mostly affects younger people. Type 2 diabetes, on the other hand, is closely linked to risk factors that can be changed, like being overweight and not being active. These results show the important of early diagnosis and focused living changes are for lowering the worldwide burden and avoiding long-term problems.Bangladesh Journal of Infectious Diseases, December 2025;12(2):228-233